2010
DOI: 10.1002/jclp.20706
|View full text |Cite
|
Sign up to set email alerts
|

Group cognitive‐behavioral therapy for depression in Spanish: culture‐sensitive manualized treatment in practice

Abstract: The authors applied cognitive-behavioral therapy (CBT) for depression using the Healthy Management of Reality treatment manual. This 16-week group treatment comprised four 4-week modules: thoughts (cognitive restructuring), activities (behavioral activation), people (interpersonal skills training), and health (addresses physical health and depression). They illustrated the use of the culture-sensitive treatment manuals by way of the member characteristics and clinical process of a Spanish-language CBT group fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 16 publications
(17 reference statements)
0
41
0
Order By: Relevance
“…In the context of rural health care, the application of cognitive behavioral techniques through brief clinical encounters or clinical outreach programs have been demonstrated to improve self‐efficacy and contribute to better mental health 39‐41 . Although there is little precedent of applying cognitive behavioral techniques with farmworkers, there is a literature suggesting their effectiveness with Latinos 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…In the context of rural health care, the application of cognitive behavioral techniques through brief clinical encounters or clinical outreach programs have been demonstrated to improve self‐efficacy and contribute to better mental health 39‐41 . Although there is little precedent of applying cognitive behavioral techniques with farmworkers, there is a literature suggesting their effectiveness with Latinos 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that many Hispanics/Latinos[as] continue to speak Spanish at home or as their primary language (DuBard & Gizlice, 2008). As such, there maybe language barrier that prevents utilization of mental health services or contributes to early attrition from therapy (Aguilera, Garza, & Munoz, 2010). A second issue is that of the variety of cultures that are Hispanic/Latino[a].…”
Section: Hispanic/latino[a] Summarymentioning
confidence: 99%
“…Studies which have examined differences in engagement between Latinos and non-Latino Whites have mostly focused on depression; these studies have found higher attrition rates in both pharmacological and psychosocial interventions for Latinos when compared to non-Latino Whites (Arnow et al, 2007; Organista et al, 1994). Additionally, problems with medication compliance, CBT attendance, and completion of CBT homework assignments among Latinos have been reported (Aguilera, Garza, & Muñoz, 2010; Ayalon, Areán, & Alvidrez, 2005; Miranda & Cooper, 2004). To our knowledge, no studies have examined engagement outcomes for Latino adults participating in a CBT intervention for anxiety disorders.…”
mentioning
confidence: 99%